Kajian Kritis Al-Ghazali terhadap Pendidikan Islam - Nazwan, Afif Putra; Anjeli, Mardawila Adha; Rahmah, Hafizhatur; Zulmuqim, Zulmuqim; Masyhudi, Fauza (AHKAM, 2023)
Education is a necessity for every human being. Therefore, it is necessary for humans to be given a good and quality education. Today, the Western world is recognized as a more advanced and civilized nation. Therefore, the West is considered more capable of providing dynamic and varied new discoveries, as well as technology that makes a significant contribution to science. So that many parts of the world are oriented towards the West, especially regarding the development of science. As a result, many generations of Muslims are no longer aware of the Islamic figures who greatly influenced the progress of the world of education, so it is important to reintroduce Islamic figures who have a great influence on the progress of education. Among them is Imam Al-Ghazali. In today's modern era, it is very necessary to know Islamic figures who make a major contribution to the progress of the world of education. So that people do not forget Islamic figures who are basically able to influence and develop education in the Islamic world. Therefore, this article will discuss "Critical Study of Al-Ghazali's Islamic Education Thought". It is hoped that this research can color and add insight and understanding of Islamic education. The type of research used is library research. This library research is a study that collects data and information from various materials contained in literary sources. Here the results and discussion explain the biography of Al-Ghazali, the concept, classification and purpose of education according to Al-Ghazali